A cone-beam computed tomography study of the mesial cervical concavity of maxillary first premolars. (August 2018) - Fan, Linfeng; Yuan, Keyong; Niu, Chenguang; Ma, Rui; Huang, Zhengwei
Highlights: There is a high prevalence of mesial cervical concavity in maxillary 1 st premolars. Two-rooted teeth have a higher incidence of such concavities than single-rooted teeth. Mesial root concavities are more prevalent in single-rooted teeth with 2 canals. Abstract: Objective: To investigate the mesial cervical concavity of maxillary first premolars and its relationship with root and canal configuration using cone-beam computed tomography (CBCT). Design: Images of maxillary first premolars (n = 1056) were collected from patients (n = 601) who had undergone in vivo CBCT scanning. The root and canal number and morphology were evaluated. The following measurements of the mesial cervical concavity of the maxillary first premolars were evaluated in section images: dentine thickness (in concavity at the cemento-enamel junction), concavity angle, depression depth (distance from mesial dentinal surface at concavity to mesial proximity), concavity position (distance from mesial dentinal wall at invagination to the top of the mesial marginal ridge). The reliability of the data was analyzed with an unpaired Student's t test and Fisher's exact test. Results: The percentages of maxillary first premolars with one root, two, and three roots were 55.5%, 43.7%, and 0.8% respectively. Mesial cervical concavity was recorded in 64.5% of single-root maxillary premolars. The prevalence of two-root maxillary first premolars with mesial cervical concavity was 73.8%. The means of the aforementioned four measurements were 1.705, 147.9, 1.640, and 5.247 mm. The values of dentine thickness (mm), depression depth (mm), and concavity position (mm) of the mesial cervical concavity were largest in two-root maxillary first premolars. The smallest concavity angle of the mesial cervical concavity was found in three-root maxillary first premolars. Conclusions: There is a high prevalence of mesial cervical concavity among maxillary first premolars. The mesial root concavity is more prevalent in single-rooted maxillary first premolars when there are two canals present, and its prevalence and degree of concavity increase with the number of roots.